THE FABRICATION AND CHARACTERIZATION OF POLY(METHYLMETHACRYLATE) (PMMA) MEMBRANE MODIFIED BY MOLECULARLY IMPRINTED POLYMERS (MIPS) FOR SEPARATION OF HUMIC ACID FROM AQUEOUS SOLUTION - RAHAYU PUTRI (NIM:20516042), TIKA
Peat water is one of surface water resources in the swampland which is generally found in Sumatera and Kalimantan. It has color range as dark brown up to black and tends to be acid. One of the largest organic compounds contained in peat water is humic acid. It is a chemical compound with high molecular weight, complex structure, and contains phenolic and carboxylic functional groups, and also builds complex compounds by binding to heavy metals in the environment. The formation of these complex compounds caused water and soil pollutions which were dangerous to human life and their environment. One of strategies for treating the peat water was achieved by reducing the presence of humic acid utilizing membrane technology using molecularly imprinted polymers (MIP) materials. The humic acid-MIPs were synthesized using microwave assisted organic synthesis (MAOS) method. The process utilized methyl methacrylate (MMA) as monomer, ethylenglycoldimethylmethacrylate (EGDMA) as crosslink agent, benzoyl peroxide (BPO) as initiator, N,N-dimethylformamide (DMF) as solvent, and humic acid as molecular mold for synthesizing the humic acid-MIPs. In addition, the non-imprinted polymers (NIPs) were produced as the comparison material to the humic acid-MIPs, without using molecular mold of humic acid. Then, the characterization for humic acid-MIPs was performed using spectroscopy methods such as Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and Electron Dispersive Spectroscopy (EDS). The FTIR characterization represented the similarity of FTIR spectra between humic acid-MIPs and non Imprinted polymers (NIPs). On the other hand, SEM analysis informed the probability of the pore formation on the surface of humic acid-MIPs was greater than NIPs materials. The poly(methylmethacrylate) (PMMA) membrane modified by humic acid-MIPs have been fabricated by dissolving the poly(methylmethacrylate) polymer into tetrahydrofuran (THF), and subsequently dispersing humic acid-MIPs into 20% (w/v) PMMA as filler solution, then the membrane was casted via inversion phase method on to the glass plate. After that, it was left out at air room and was soaked in coagulant bath (aquades). The characterization of the membranes was performed to study its permeability properties and to analyze its FTIR spectra. The FTIR spectra of membranes indicated that there was no significant distinction between PMMA and PMMA-MIPs membranes because of their constituent monomer of humic acid-MIPs was identical to the membrane polymers. The morphology analysis of PMMA and PMMA-MIPs membranes illustrated that both membranes have different pore size, thus it can be concluded that the producing membrane in this study was asymmetric membrane. The membrane flux was gradually increased by increasing of given pressure. The flux value of PMMA-MIPs was higher than PMMA membranes. According to the result, the water permeability values for PMMA, PMMA-MIPs membrane were 9.402 Lm-2h-1bar-1 and 32.142 Lm-2h-1bar-1, respectively. The PMMA membrane showed the rejection value as 68.99% at pH 5, whereas the PMMA-MIPs membrane displayed the percentage for rejection as 76.62% at pH 3. The backwash of membrane using 0.1 M NaOH solution improved the membrane flux. The flux value of PMMA membrane has enhancement up to 82.85% from its original state after backwash, while the flux value of PMMA-MIPs increased up to 31.24% from its original state.